Polyamines: total daily intake in adolescents compared to the intake estimated from the Swedish Nutrition Recommendations Objectified (SNO) - Mohamed Atiya Ali; Eric Poortvliet; Roger Strömberg; Agneta Yngve (Food & Nutrition Research, 2011)
Background: Dietary polyamines have been shown to give a significant contribution to the body pool of polyamines. Knowing the levels of polyamines (putrescine, spermidine, and spermine) in different foods and the contribution of daily food choice to polyamine intake is of interest, due to the association of these bioactive amines to health and disease. Objective: To estimate polyamine intake and food contribution to this intake in adolescents compared to a diet fulfilling the Swedish Nutrition Recommendations. Design: A cross-sectional study of dietary intake in adolescents and an ‘ideal diet’ (Swedish nutrition recommendations objectified [SNO]) list of foods was used to compute polyamine intake using a database of polyamine contents of foods. For polyamine intake estimation, 7-day weighed food records collected from 93 adolescents were entered into dietetic software (Dietist XP) including data on polyamine contents of foods. The content of polyamines in foods recommended according to SNO was entered in the same way. Results: The adolescents’ mean daily polyamine intake was 316±170 µmol/day, while the calculated contribution according to SNO was considerably higher with an average polyamine intake of 541 µmol/day. In both adolescent's intake and SNO, fruits contributed to almost half of the total polyamine intake. The reason why the intake among the adolescents was lower than the one calculated from SNO was mainly due to the low vegetable consumption in the adolescents group. Conclusions: The average daily total polyamine intake was similar to that previously reported in Europe. With an ‘ideal’ diet according to Swedish nutrition recommendations, the intake of this bioactive non-nutrient would be higher than that reported by our adolescents and also higher than that previously reported from Europe.